2010
DOI: 10.1097/bpo.0b013e3181ec0853
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot Classification

Abstract: Prognostic Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…P. J. Dyer found that the initial Pirani score had a strong link ( r = 0.72, P = 0.0005) to the number of casts, and the correlation remained very high (0.66 and 0.79) when the patients were subdivided into tenotomy and non-tenotomy group, respectively 14 . In contrast, a study of 123 patients found the ICC for the initial total Pirani and Dimeglio scores and number of casts were 0.33 and 0.34, respectively 15 . Another study showed low ( r = 0.21) or no ( r = 0.12) correlation between initial Dimeglio or Pirani score, respectively, and the number of casts, as did the equinus ( r = 0.21) and adduction ( r = 0.17) individual components of the Dimeglio score, and posterior crease ( r = 0.09) or adduction ( r = 0.17) for the individual components of the Pirani score 11 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…P. J. Dyer found that the initial Pirani score had a strong link ( r = 0.72, P = 0.0005) to the number of casts, and the correlation remained very high (0.66 and 0.79) when the patients were subdivided into tenotomy and non-tenotomy group, respectively 14 . In contrast, a study of 123 patients found the ICC for the initial total Pirani and Dimeglio scores and number of casts were 0.33 and 0.34, respectively 15 . Another study showed low ( r = 0.21) or no ( r = 0.12) correlation between initial Dimeglio or Pirani score, respectively, and the number of casts, as did the equinus ( r = 0.21) and adduction ( r = 0.17) individual components of the Dimeglio score, and posterior crease ( r = 0.09) or adduction ( r = 0.17) for the individual components of the Pirani score 11 .…”
Section: Discussionmentioning
confidence: 87%
“…One of the questions most frequently asked by parents is how many casts will be needed before correcting the deformity, and accurately informing the parents improves patient treatment compliance. Several studies have investigated the correlation between initial Pirani score or Dimeglio score with the numbers of casts needed to acquire full correction of the deformity, but there is no consensus conclusion that has been drawn 11 , 13 15 . To our knowledge, there is no study that has investigated the correlation between initial Pirani score or Dimeglio score and the numbers of casts needed at different severities of the deformity.…”
Section: Introductionmentioning
confidence: 99%
“…These scores can predict the number of casts required, need for tenotomy and recurrences, but cannot predict compliance with the FAO which is imperative for a successful outcome at long term 8242526. A relapsed clubfoot after Ponseti technique rarely present as an untreated clubfoot.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there has not been accepted unified opinion concerning clear correlation between clinical examination prior to treatment obtained by scoring systems and the outcomes of the treatment in published papers. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%